2019
DOI: 10.7196/samj.2019.v109i5.13789
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis transmission in a hospitalised neonate: Need for optimised tuberculosis screening of pregnant and postpartum women

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…With appropriate treatment and close follow-up, pregnant women sick with TB can be cured and have positive maternal outcomes. Integration of TB screening programs with maternal care services could be an efficient way to detect cases in women that might otherwise remain undetected, as most TB in pregnancy is diagnosed in the third trimester of pregnancy or in the postpartum period [3,4,22,23]. Another 2017 systematic review and meta-analysis including 13 studies found that TB disease in pregnancy is associated with adverse maternal and perinatal outcomes [7].…”
Section: Discussionmentioning
confidence: 99%
“…With appropriate treatment and close follow-up, pregnant women sick with TB can be cured and have positive maternal outcomes. Integration of TB screening programs with maternal care services could be an efficient way to detect cases in women that might otherwise remain undetected, as most TB in pregnancy is diagnosed in the third trimester of pregnancy or in the postpartum period [3,4,22,23]. Another 2017 systematic review and meta-analysis including 13 studies found that TB disease in pregnancy is associated with adverse maternal and perinatal outcomes [7].…”
Section: Discussionmentioning
confidence: 99%
“…This includes preeclampsia, intrauterine growth delay, prenatal bleeding, low birth weight, low Apgar score at birth, and early fetal death. 22 , 23 Early treatment can reverse this negative effect on perinatal outcomes. Late diagnosis and incomplete or partial pharmacotherapy are associated with poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Care units, to prevent exposure and transmission of TB to vulnerable neonates, mothers and healthcare workers. [20]…”
Section: In Practicementioning
confidence: 99%